Assessment of Land Erosion Hazard in the Sampean Hulu Sub Watershed, Bondowoso Regency - Setyawan, Roeby; Nurtjahjaningtyas, Indra; Hidayah, Entin (Fakultas Teknik, Universitas Brawijaya, 2023)
The Sub-watershed of Sampean Hulu, located on the slopes of Mount Raung is susceptible to erosion hazards. Erosion indicators have been observed in the irrigation channels, mainly due to frequent sedimentation, which compromises the irrigation infrastructure's optimization and water distribution. To address this, erosion monitoring using the Universal Soil Loss Erosion (USLE) model, along with GIS and remote sensing techniques, is essential. It was found that the irrigation networks associated with Clangap and Tamanan rain gauges are at higher risk due to intense rainfall. Maesan and Wonosari II rain gauges cover a larger irrigation network area, highlighting the need for erosion prevention measures. The dominant soil type, Tv, with a high clay content, is highly susceptible to erosion. Flat and gently sloping slopes have a lower risk compared to steeper slopes, while very steep and steep slopes pose higher erosion risks. Paddy fields and well-managed forest plantations have lower erosion hazards, while bare land and certain agricultural practices contribute to increased erosion risks. The analysis classified the erosion hazard into five classes, with the sub-watershed being predominantly low and very low susceptible to soil erosion. Implementing conservation practices, sustainable land management, and land use regulations are crucial for erosion prevention.